Peran Diversifikasi Unit Usaha Dalam Meningkatkan Kinerja Koperasi: Studi Kasus Koperasi Karyawan Pt Pelindo Regional 4 Makassar - Nanda Rezky Pratama; Alamsyah; Aprilia , Firda; Fitrawati Nur; Nur Restu Idris (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the role of business unit diversification in improving the performance of the PT Pelindo Regional 4 Makassar Employee Cooperative from a management and institutional economics perspective. The study uses a case study approach with a SWOT analysis method to identify internal and external factors that influence cooperative performance. Data were collected through semi-structured interviews with business unit administrators and managers and focus group discussions (FGDs) with cooperative members, supported by analysis of internal cooperative documents. The results show that business unit diversification, which includes the retail sector, savings and loans, and entrepreneurship training, can create cash flow synergy, increase member loyalty, and strengthen the cooperative's economic resilience. Institutional support from the parent company is a strategic factor in strengthening the legitimacy and access to resources for cooperatives. However, the study also identified several challenges, including limited management professionalization, low digital innovation, and suboptimal coordination between business units. Opportunities for cooperative development are open through partnerships with fintech companies, the use of financial inclusion policies, and the digital transformation of cooperative services. This study recommends strengthening governance, increasing managerial capacity, and digitizing business units as key strategies to improve cooperative performance and sustainability amidst modern economic competition. The research findings are expected to provide practical contributions to the development of adaptive and competitive cooperative management models